Some Improvements on an Algorithm for Controlled Selection - LIN, Ting Kwong (Institutional Knowledge at Singapore Management University, 1992)
The sampling technique called controlled selection was f'irst described by Goodman and Kish (1950). It was found to be a very useful sampling technique among practicing survey samplers, especially in selecting first-stage units in multi-stage sampling. Hess, Riedel and Fitzpatrick (1961, 1975) have given a simple illustration on how it can be implemented in the sampling of hospitals in the state of Michigan. In this paper, we show how the Groves-Hess algorithm can be improved and how further controls which are useful to survey practitioners can be built into the algorithm. Problems the old algorithm could not solve can now be solved by the new algorithm.